Effects of different concentrations of Aspergillus Niger on fermentation characteristics and nutritive value of Dwarf Napier grass silage - Hireshaa Asogan; Mohammad Mijanur Rahman; Laila Naher; Md. Safiul Alam Bhuiyan (UMK Publisher, 2025)
Dwarf Napier grass is considered to be low-quality grass due to its low nutritional value if used at an inappropriate cutting age. This study was aimed at investigating the effect of Aspergillus Niger on the improvement of dwarf Napier grass silage quality. The 60-days old of dwarf Napier grass were mixed with 7% molasses and A. Niger at a rate of 0 (T0), 10 6 (T1) and 10 7 spores/ml (T2). Each kg of plant materials was mixed with 10.7ml fungal substrate and ensiled for 45 days. According to the results of this study, the pH tended to decrease with an increased rate of A. Niger, while the lactic acid content tended to increase. The T1 silage showed lower (p<0.05) ash content than others. Non-significant (p>0.05) differences were observed on other proximate components. An increasing trend was observed in crude protein content with an increasing rate of A. Niger, while no consistent trend was observed in crude fiber content. In conclusion, A. Niger could be used as an additive to enhance the silage quality, but further research is needed to know the nature of the mode of action of A. Niger in silage.